2015
DOI: 10.1159/000437056
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effect of Apigenin on Pharmacokinetics of Venlafaxine in vivo and in vitro

Abstract: Objective: This study was conducted to investigate the effects of orally administered apigenin on the pharmacokinetics of venlafaxine (VEN) in rats and on the metabolism of VEN in human and rat liver microsomes in vitro. Methods: Ten healthy male SD rats were randomly divided into 2 groups: A group (control group), B group (a single dose of 250 mg/kg apigenin). A single dose of 20 mg/kg VEN was administered orally 30 min after administration of apigenin (250 mg/kg). VEN plasma levels were measured by HPLC with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Furthermore, the presence of apigenin may be a contributing factor to improve the systemic exposure of other CYP2C9 substrates such as (S)-warfarin, tolbutamide, phenytoin, and acenocoumarol in vivo [19] . And our previous studies indicated that the coadministration in rat with apigenin could increase the absorption of imatinib and venlafaxine [29,30] . Meanwhile, further interaction investigations between apigenin and clinical drugs in vivo studies should be carried out.…”
Section: Discussionmentioning
confidence: 95%
“…Furthermore, the presence of apigenin may be a contributing factor to improve the systemic exposure of other CYP2C9 substrates such as (S)-warfarin, tolbutamide, phenytoin, and acenocoumarol in vivo [19] . And our previous studies indicated that the coadministration in rat with apigenin could increase the absorption of imatinib and venlafaxine [29,30] . Meanwhile, further interaction investigations between apigenin and clinical drugs in vivo studies should be carried out.…”
Section: Discussionmentioning
confidence: 95%
“…The experiment of inhibition percentage of Apa was measured by the generating rate of metabolite in the presence of 100 μM Apa (study group) compared with no inhibitor (control group). In the experiment of IC 50 determination, the concentration of Apa was set as 0.01, 0.1, 1, 10, 50 and 100 μM, while that of Ven was 100 μM, which is close to its K m value . In the experiment of determining the inhibitory effect of Apa on Ven in RLM and HLM, the concentration of Apa was designed at 0, 2, 5 and 10 μM according to the IC 50 value, while the concentration of Ven was designed at 25, 50, 100, 200 μM according to the K m value.…”
Section: Methodsmentioning
confidence: 99%
“…In view of the potential of Apa in the field of anticancer drugs and the widespread use of Ven in the field of antidepressant drugs, it makes sense to study whether there is an interaction between the two drugs. To our knowledge, there are no studies regarding these two drugs in combination, but there are some similar methods about interactions of Ven and Apa with other compounds, like the effect of apigenin on Ven and the effect of Apa on carvedilol . In this study, we examined the pharmacokinetics of Ven in rats after administration of Apa and identified the effect as well as the mechanisms of Apa on Ven in human and rat liver microsome.…”
mentioning
confidence: 99%
“…Rats were randomly divided into two groups: group A and group B (six rats per group). Rats in group A were orally given VEN at 20 mg/kg and in group B were given VEN at 20 mg/kg and FLX at 10 mg/kg . All drugs were given by gastric gavages after 12 h food deprivation.…”
Section: Methodsmentioning
confidence: 99%
“…Hefner et al reported that melperone has a clinically relevant inhibitory potential on CYP2D6 thus increasing the serum concentrations of VEN and decreasing the metabolic ratios of ODVEN/VEN. Zhan et al demonstrated that an intake of apigenin could increase VEN plasma levels and some of its pharmacokinetic parameters (AUC, T max ). Therefore, the potential toxic concentration of VEN can be caused by reduced metabolic capacity .…”
Section: Introductionmentioning
confidence: 99%